PENGEMBANGAN GAME EDUKASI BERBASIS WORDWALL TERINTEGRASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING MATERI WUJUD ZAT DAN PERUBAHANNYA - Widiana, Risky; Tyas, Dewi Nilam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to develop, test the feasibility, and effectiveness of an educational game based on Wordwall integrated with the Problem Based Learning model for the subject of matter states and their changes at SDN Jali 1, Demak District. The research method used is Research and Development (R&D) with the ADDIE model. The result of the research is an educational game media on Wordwall using templates from gameshow quiz, maze chase, and spin the wheel. The feasibility test for material and media obtained percentages of 100% and 90%, classified as “very feasible”. Teacher responses yielded 98.3% and student participants 98% in the small-scale media trial and 98% in the large-scale media trial, classified as “very feasible”. The normality test for pretest and posttest data was declared ‘normally distributed’. The t-test results obtained a t-value (16.212) greater than the t-table (2.086), thus Ho was rejected, and the N-Gain test scored 0.77, classified as “high”. Based on this description, it is concluded that an educational game based on Wordwall integrated with the Problem Based Learning model for the subject of matter states and their changes has been successfully developed, which is very feasible and effective in enhancing critical thinking abilities.